Morpholinium and Piperidinium Based Deep Eutectic Solvents for Synthesis of Pyrazole‐5‐Carbonitriles, Indoles and Tetrazoles: Bulk Properties via Molecular Dynamics Simulations. Issue 45 (5th December 2018) - Sanam,; Bux, Khair; al‐Rashida, Mariya; Alharthy, Rima D.; Moin, Syed T.; Hameed, Abdul
Abstract: Deep eutectic solvents (DES) have gained much popularity in the area of green synthetic chemistry, since they act as excellent alternative to traditional organic solvents for carrying out diverse organic reactions and transformations. Furthermore, they are thermally stable over a wide temperature range, they are non‐volatile, inert and can be easily recovered and reused after carrying out reactions. In the present study, we have synthesized morpholine and piperidine based ionic liquids, and combined them with different hydrogen bond donors (urea, diethylene glycol (DEG), carboxylic acid, thiourea, ethanol and methanol) to produce different DES melts. These DES melts were then explored for their potential as catalyst/reaction media for carrying out different organic transformations for synthesis of molecules such as pyrazole‐5‐carbonitriles5 a‐d, Fisher Indoles8 a‐d and 1 H ‐tetrazoles10 a‐b . In DES, the hydrogen bonded interactions between ionic liquids and hydrogen bond donors are known to be crucial for mediating their catalytic and synthetic efficiency, hence molecular dynamics simulations of these DES melts were carried out to investigate and study these effects. Abstract : Deep eutectic solvents (DES) have gained significant attention in synthetic organic chemistry. In the current study, morpholine and piperidine based ionic liquids in combination with different hydrogen bond donors (urea, diethylene glycol (DEG), carboxylic acid, thiourea, ethanol and methanol) were employed as DES melts to carry out different organic reactions. Moreover, the molecular dynamics simulations of DES melts were also carried out to study hydrogen bonded interactions between ionic liquids and hydrogen bond donors (HBD).